Current Trends in Retirement: Implications for Career Counseling and Vocational Psychology. (June 2015) - Lytle, Megan C.; Clancy, Megan E.; Foley, Pamela F.; Cotter, Elizabeth W.
This article provides an overview of emerging trends in retirement, examines demographic trends in the labor force, and provides practical recommendations for working with older workers across cultures (e.g., women and racial/ethnic minorities, and among others). Increasingly, older workers in the United States remain in the workforce for reasons related to financial security, health care, and personal fulfillment. Although retirement trends have become more complex, there is limited empirical literature addressing this issue and the research available does not attend to the needs of a diverse workforce. Therefore, implications for training, practice, advocacy, and research with regard to working with older workers across cultures (e.g., women and racial/ethnic minorities, among others) are provided.